Enhancing Religious Behavior and Well-being in Elderly Through Majelis Taklim Al-Sulthan: A Case Study - Muhammad Noor Fallah (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: This study investigates the role of Majelis Taklim Al-Sulthan in improving religious behavior and mental well-being among elderly participants. Employing a descriptive qualitative approach, the research delves into the methods and processes used by Majelis Taklim Al-Sulthan and identifies the factors that support and hinder its effectiveness. Data were collected through direct observation, in-depth interviews with religious leaders and elderly participants, and documentation of spiritual activities. Findings reveal that Majelis Taklim Al-Sulthan significantly enhances elderly individuals' religious behavior through educational programs on Islamic teachings, supports social cohesion, and addresses mental health issues. The study underscores the importance of such institutions in providing spiritual and social support to older people, contributing to their overall quality of life. Limitations include the study's focus on a single location and its qualitative nature, suggesting a need for broader research. Recommendations include developing policies and programs to sustain and enhance Majelis Taklim's role in supporting elderly individuals. Abstrak: Penelitian ini mengkaji peran Majelis Taklim Al-Sulthan dalam meningkatkan perilaku keagamaan dan kesejahteraan mental di kalangan lansia. Menggunakan pendekatan deskriptif kualitatif, penelitian ini mengeksplorasi metode dan proses yang diterapkan oleh Majelis Taklim Al-Sulthan serta mengidentifikasi faktor-faktor yang mendukung dan menghambat efektivitasnya. Data dikumpulkan melalui observasi langsung, wawancara mendalam dengan tokoh agama dan peserta lansia, serta dokumentasi aktivitas keagamaan. Temuan penelitian menunjukkan bahwa Majelis Taklim Al-Sulthan secara signifikan meningkatkan perilaku keagamaan lansia melalui program pendidikan tentang ajaran Islam, mendukung kohesi sosial, dan menangani masalah kesehatan mental. Penelitian ini menekankan pentingnya lembaga semacam ini dalam memberikan dukungan spiritual dan sosial kepada lansia, yang pada gilirannya berkontribusi pada kualitas hidup mereka secara keseluruhan. Keterbatasan studi mencakup fokus pada lokasi tunggal dan sifat kualitatifnya, yang menunjukkan perlunya penelitian lebih luas. Rekomendasi termasuk pengembangan kebijakan dan program untuk mempertahankan dan meningkatkan peran Majelis Taklim dalam mendukung lansia.